Antioxidant Assay and Total Flavonoid Determination of Ethanolic Extract of Walnut (Canarium indicum L.) Leaves and Its Fractions - Lukmanto, Lukmanto; Fadhila, Nadila Ikhda Ramadhani; Wulandari, Lestyo; Puspitasari, Endah (Jurnal ILMU DASAR, 2023)
Antioxidants are compounds that inhibit free radicals. Many plants have antioxidant activity because they contain antioxidant compounds such as flavonoids. This study aimed to evaluate the antioxidant activity, phytochemical contents, total flavonoid content and to establish the relationship of total flavonoid content and antioxidant activity of extract and fractions of walnut (Canarium indicum L.) leaves. Antioxidant activity of ethanolic extract, n-hexane fraction, ethyl acetate fraction, and ethanolic-water fraction of walnut leaves was examined by using the DPPH method and determination of total flavonoid content was determined spectrophotometrically. The results showed that antioxidant activity of ethanolic extract, n-hexane fraction, ethyl acetate fraction, and ethanolic-water fraction based were 25.294 ± 0.055; 175.245 ± 0.4999; 20.135 ± 0.009; and 28.806 ± 0.0424 μg/ml, respectively. The phytochemical content of ethanol extract of walnut leaves are saponins, flavonoids, tannins, and polyphenols. The total flavonoid content of ethanolic extract, n-hexane fraction, ethyl acetate fraction and ethanolic-water fraction were 2.624 ± 0.012; 0.499 ± 0.023; 3.846 ± 0.006; and 1.596 ± 0.006 gram quercetin equivalent/gram extract, respectively. Correlation between antioxidant activity and total flavonoid content revealed that 63.2 % of antioxidant activity was influenced by the presence of flavonoid compounds.